Multi-node processing for asymmetrical communications in underwater acoustic networks - Silva, A. (2014)
Underwater acoustic communication networks have attracted attention for its applications in many areas such as mine warfare, rapid environmental assessment or search and rescue, where there is the need for conserted action of a group of observers/actuators. A common requirement in most of these applications is the need to make accessible to the global (terrestrial/aerial) user network large amounts of critical underwater collected data. This paper addresses this requirement by using multichannel nodes providing an asymmetrical point-topoint (P2P) connection where the upload link has a much higher data rate than the download link. The emphasis of this work is not so much on the final channel throughput but on establishing the optimal processing of spatially distributed multichannel nodes that serve as interface between the underwater nodes and the global/user network. The adopted strategy relies on passive time-reversal which can be viewed as a spatial pre-equalizer for each multichannel node. Then an intersymbol interference optimal combination of various nodes is divised for balancing poor communications of one or more nodes in the network. The method and techniques are theoretically derived and applied to real data acquired with a network of 2 surface buoys over an environmentally challenging area off the coast of Portugal in July 2007.